Arthroscopic Biological Total Shoulder Resurfacing: An Alternative Surgical Technique and Treatment Option for Arthritic Shoulder Pain in Young to Middle-aged Adults. Issue 1 (March 2018) - Kovack, Thomas J.; Long, Anthony
Abstract : Glenohumeral shoulder arthritis seems to be growing in prevalence, especially in the younger population below 50 years old. This may be due to multiple factors such as heredity, trauma, iatrogenic postsurgical changes, and high vocational and recreational demands. These factors increase the risk and incidence of glenohumeral osteoarthritic degeneration as we age. This arthritic degradation of the articular surfaces in the shoulder leads to symptoms of loss of mobility, pain, and functional limitation. The surgical treatment for glenohumeral arthritis in the young to middle aged, active adult has been the source of controversy and debate within the orthopedic community. A relatively new surgical procedure, arthroscopic biological total shoulder resurfacing, has the potential to provide significant pain relief and improve functional outcomes while allowing for return to high-level activity without the restrictions and complications that accompany other surgical interventions. This article will discuss in detail the surgical technique, rationale, and postoperative care of this biological resurfacing technique.